SATUAN DAN PENGUKURAN TRADISIONAL MENGGUNAKAN TANGAN OLEH MASYARAKAT DI KANAGARIAN KINARI: KAJIAN ANTROPOLINGUISTIK (Traditional Unity and Measures Using Hands by Kinari Villagers: Anthropolinguistic Study) - Imron Hadi (SALINGKA, 2016)
The longer traditional unity and measures using hands and the rarer used by villagers because they have used the modern one which have high accuracy, precision, and low margin error.Because of that, this study is aimed to find out the traditional unity and measures using hands which is still used by Kinari Villagers in Solok Regency with descriptive qualitative methodthrough observation, field note, open-ended interview to some informen. The data are analyzed with triangulation by direct division-share technique. The result of this research shows thatthere are two kinds of measures and unity: first is for measuring length, such as dapo, eto, jangka, jari,and rueh: second is for measuring volume, such as ganggam, binjek, kauik, kapa,pacik, sauek, suok, culiak, paluak, and patiak. In conclusion, the traditional measures and unity are only used by the old generation, and the young generation use the modren one which has high precision, accuracy and low margin error.